Development of catalyst-free carbon-sulfur bond formation reactions under aqueous media and their applications - Min Sun Kang; Joycelyn Yi Xin Khoo; Zhenhua Jia; Teck-Peng Loh (Green Synthesis and Catalysis, 2022)
Methods for the carbon-sulfur bond formation under catalyst-free, aqueous conditions are extremely useful in organic synthesis and chemical biology. Our laboratory has developed methodologies to construct carbon-thiol bonds, carbon-sulfinic acid bonds, and carbon-disulfide bonds and such methodologies have been widely adopted by other research groups over multidisciplinary fields. In this article, our work on C–S bond formation in an aqueous solvent and its corresponding applications is summarized.